2007
DOI: 10.1111/j.1365-4632.2007.03218.x
|View full text |Cite
|
Sign up to set email alerts
|

Change in pattern of skin disease in Kaduna, north‐central Nigeria

Abstract: These changes in skin disease can be attributed mainly to an increase in urbanization and improved socio-economic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
58
9
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 25 publications
15
58
9
1
Order By: Relevance
“…[1][2][3][4] Acne is also the most common skin disease in adults. 5 The proportions of acne vulgaris in hospital-based studies of skin disease in Africa have been reported to be 4.6% in Ghana, 6 6.7% in Nigeria, 7 and up to 17.5% in South Africa. 8 Although, in a preliminary study of the dermatologic needs of a small rural community in Ethiopia, Figueroa et al .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Acne is also the most common skin disease in adults. 5 The proportions of acne vulgaris in hospital-based studies of skin disease in Africa have been reported to be 4.6% in Ghana, 6 6.7% in Nigeria, 7 and up to 17.5% in South Africa. 8 Although, in a preliminary study of the dermatologic needs of a small rural community in Ethiopia, Figueroa et al .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Community-based studies in Nigeria have reported prevalence rates of skin diseases (or dermatophytoses alone) between 10% and 64%. 1,13,[22][23][24][25][26][27] The most common skin condition was fungal infections, especially tinea capitis among school-age children, especially boys, accounting for 43% of the skin diseases in the community.…”
mentioning
confidence: 99%
“…32 Common skin manifestations related to HIV/AIDS were pruritic papular eruption and seborrhoeic dermatitis, followed by herpes zoster, dermatophytosis, candidiasis, molluscum contagiosum, xeroderma, and drug eruptions. 20,33,34 In a setting with a high HIV prevalence, such skin manifestations are predictors for the presence, progression, and severity of the HIV infection. In a study by Ukonu and Eze 34 in south Nigeria, 55% of all the patients attending the dermatology clinic were HIV/AIDS patients and presented with multiple skin diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the teenage years, the prevalence in women again tends to be higher than in men. It has been reported by Yahya (2009), that the proportions of acne vulgaris in hospital-based studies of skin disease in Africa have been reported to be 4.6% in Ghana, 6.7% in Nigeria (Yahya 2007) and up to 17.5% in South Africa (Hartshorne, 2003;Yahya, 2009). Acne vulgaris is very common in adolescents in Nigeria, with a prevalence ranging from 35%-90.7% (Ogunbiyi, Omigbodun, and Owoaje, 2009) in community-based surveys across the nation; it has also consistently ranked among the ten most common reasons for consultations in dermatologic outpatient clinics in both the northern and southern parts of the country (Yahya, 2009).…”
Section: Background Of Studymentioning
confidence: 99%